A methodology for risk-based management of the remaining life of structures in vertical mine shafts through integrated structural inspection and maintenance - Heyns, P.S. (Philippus Stephanus) (University of Pretoria, 2025)
Dissertation (MEng (Physical Asset Management))--University of Pretoria, 2024.